Upaya Guru Membantu Anak Berkebutuhan Khusus yang Mengalami Kesulitan Belajar di SDI Bung. - Frans Laka Lazar (Jurnal Pendidikan dan Kebudayaan Missio, 2023)
There is a special issue faced at SDI Bung, namely there are students who have reading difficulty, writing difficulty, and calculating difficulty even though they are already in the high grade (grades 4, 5 and 6). They are grouped in children with special needs. They could not distinguish letters and interpret them, copy handwriting and put it in sentences, distinguish signs, symbols or numbers. The research aims are to find out the types of learning difficulties of children with special needs at SDI Bung and the efforts of teachers to overcome it. The method used in this research is descriptive qualitative with interview technique. The results showed that there were three types of learning difficulties for children with special needs at SDI Bung, namely reading difficulties (dyslexia), writing difficulties (dysgraphia), and calculating difficulties (dyscalculia). Toward these three difficulties, the teacher tries to help them by providing instructions according to the level of error such as entering the alphabet, practicing combining letters into words (dyslexia); training students to trace letter shapes and practice copying text (dysgraphia); and make basic practical exercises using visual aids, intensive guidance and provide teaching according to the level of complexity (dyscalculia). Seeing the three types of learning difficulties for children with special needs above, the researchers suggest that teachers at SDI Bung must train students in the three basic skills, namely reading, writing and counting in lower grades until they master them.